2016
DOI: 10.1007/s40806-016-0055-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Behaviour and Face Encoding in a Hypothetical Real-World Social Contract: Handwashing in Hazardous Health Settings

Abstract: Investigations into the evolutionary origins of human cognition has shown that individuals' memory for others is influenced by the latter's behaviour in social contracts. Such research is primarily based on hypothetical or more abstract forms of social contracts, whereas an application of this knowledge to everyday health behaviours can be of great value. To address this, the current study investigated whether participants who were asked to imagine themselves in a hypothetical hazardous health scenario showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Few studies examined face recognition with multiple faces at once and even fewer investigated tagging faces with different behaviours, a common behaviour in social gatherings and relevant information in eye witnesses' reports. The findings from earlier studies showed a range of face recognition biases in social scenarios, from biases towards cooperators (cf., Barclay, 2004) or free-riders (cf., Cosmides, Tooby, Fiddick, & Bryant, 2005), to reports of no biases towards either of them (cf., Felisberti & Farrelly, 2016). One such study revealed recognition biases towards faces tagged with a cooperative rather than neutral or cheating behaviour (Felisberti & Pavey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Few studies examined face recognition with multiple faces at once and even fewer investigated tagging faces with different behaviours, a common behaviour in social gatherings and relevant information in eye witnesses' reports. The findings from earlier studies showed a range of face recognition biases in social scenarios, from biases towards cooperators (cf., Barclay, 2004) or free-riders (cf., Cosmides, Tooby, Fiddick, & Bryant, 2005), to reports of no biases towards either of them (cf., Felisberti & Farrelly, 2016). One such study revealed recognition biases towards faces tagged with a cooperative rather than neutral or cheating behaviour (Felisberti & Pavey, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…By showing that face recognition and source memory are affected by information specific to trustworthiness rather than for autobiographical information in general, this is the first study to show that this is not a general facet of human memory, but instead can be adaptive in specifically aiding the ability to detect potential cooperators and/or cheaters in social exchanges. Further research can examine how different autobiographical information about others affects decision making, with the aims of applying this knowledge to real world scenarios, such as health behaviours (Felisberti & Farrelly, 2016) and also furthering our understanding of how our different cognitive capacities may be adaptive. Furthermore, by identifying these key influences, we will know more about how adaptive our ability is to deal with the wealth of information we gain about others in various social interactions.…”
Section: Discussionmentioning
confidence: 99%